2023
DOI: 10.1101/2023.10.23.563669
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Migraine inhibitor olcegepant reduces weight loss and IL-6 release in SARS-CoV-2 infected older mice with neurological signs

Shafaqat M. Rahman,
David W. Buchholz,
Brian Imbiakha
et al.

Abstract: COVID-19 can result in neurological symptoms such as fever, headache, dizziness, and nausea. We evaluated whether the Calcitonin Gene-Related Peptide (CGRP) receptor antagonist, olcegepant, used in migraine treatment could mitigate acute neuroinflammatory and neurological responses to SARS-COV-2 infection. We infected wildtype C57BL/6J and 129/SvEv mice, and a 129 αCGRP-null mouse line with a mouse-adapted SARS-CoV-2 virus, and evaluated the effect of CGRP receptor antagonism on the outcome of that infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…It can regulate the metabolism of calcium and phosphorus in the body and participate in the balance of calcium and phosphorus in the body. High levels of calcitonin may be caused by diseases such as medullary thyroid cancer, small cell lung cancer, and medullary thyroid cancer, as well as by bacterial or fungal infections, allergies, and other reasons [30].Our research results indicate that the 2 groups showed a signi cant increase in IL-6(P < 0.01)(Table 4) and Calcitonin(P < 0.01)(Table 4) at 24 h after surgery, 96 h after surgery(P < 0.01)(Table 4) and 144 h after surgery.The levels of IL-6(P < 0.05)(Table 4)and Calcitonin in the Non-naloxone group were signi cantly higher at 24 h after surgery in Table 4.These results indicate that perioperative naloxone use can delay the rise rate of IL-6 and calcitonin in postoperative gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…It can regulate the metabolism of calcium and phosphorus in the body and participate in the balance of calcium and phosphorus in the body. High levels of calcitonin may be caused by diseases such as medullary thyroid cancer, small cell lung cancer, and medullary thyroid cancer, as well as by bacterial or fungal infections, allergies, and other reasons [30].Our research results indicate that the 2 groups showed a signi cant increase in IL-6(P < 0.01)(Table 4) and Calcitonin(P < 0.01)(Table 4) at 24 h after surgery, 96 h after surgery(P < 0.01)(Table 4) and 144 h after surgery.The levels of IL-6(P < 0.05)(Table 4)and Calcitonin in the Non-naloxone group were signi cantly higher at 24 h after surgery in Table 4.These results indicate that perioperative naloxone use can delay the rise rate of IL-6 and calcitonin in postoperative gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…CGRP’s role in inflammation, pain transmission, and in evoking sensory hypersensitivities has supported therapeutic efforts to block CGRP signaling for migraine [ 58 ] and COVID therapy [ 59 ]. Yet others have found CGRP to act as a neuromodulator with neuroprotective effects [ 60 ].…”
Section: Discussionmentioning
confidence: 99%